An estimate of expected economic losses from satellite collisions with orbital debris. Issue 1 (March 2023) - Adilov, Nodir; Braun, Vitali; Alexander, Peter; Cunningham, Brendan
Abstract: We estimate the expected annual cost of satellite collisions with orbital debris and find that the expected annual loss for all orbits was 86-103 million in 2020. Nearly all expected losses, 79-102 million, were in LEO, and these losses represent approximately 0.16% of the value of operational satellites in that orbit. Over 70% of losses occurred in the 600-900 km orbital band. Commercial satellites' share of expected losses is approximately one-third of expected total losses. These findings may have implications for policy, in particular relating to the market for active debris removal.